Functional autonomy and sarcopenia markers in women over 55 years of age (2021)
ABSTRACT: Introduction: Some parameters used to diagnose sarcopenia and functional autonomy dis-orders can lead to interpretation and classification errors.Objective: To analyze sarcopenia markers and their relationship with the strength and gait of physically active older women aged between 55 and 76 years. Materials and Methods: Analytical observational study conducted in 178 physically active Colombian women who were distributed in two age groups (group 1: 55-66 years, n=98, and group 2: 67-76 years, n=80). A multiple linear regression model was used to establish possible correlations between strength and gait indicators (dependent variables) and body composi-tion (independent variables). Results: Fat mass and appendicular mass (appendicular lean/height2(kg/m2)) explained power variance in the lower limbs in group 1 (G1) (SJ: p=0.001, R2=0.56; CMJ: p=0.001, R2=0.51; CM-JAS: R2=0.60, p=0.001). Similar results were observed in group 2 (G2) (SJ: R2=0.32, DW1=2.14; CMJ: R2=0.51, DW2=2.38; CMJAS: R2=0.41, DW3=2.56). Furthermore, fat mass explained vari-ance in gait pattern in G1 and G2 differently (G1: p=-0.006; R2=20%; G2: p=-0.001; R2=29%). Conclusion: Recording fat and appendicular mass allow studying negative changes in lower limb strength and their effect on gait pattern, as well as identifying the type of sarcopenia and functional autonomy disorders in physically active Colombian women aged 55 to 76 years.Keywords: Sarcopenia; Muscle Strength; Hand Strength; Body Composition; Elderly (MeSH)